Adapting to climate variability and change in rural Kenya: farmer perceptions, strategies and climate trends. (9th December 2016) - Ochieng, Justus; Kirimi, Lilian; Makau, Joyce
Abstract : Climate change has had a significant impact on rain‐fed agricultural production in developing countries. Smallholder farmers are the most vulnerable, and currently must make production decisions in a high risk and uncertain environment with regard to rainfall and temperature. This paper uses climate and household survey data to analyse farmer perceptions regarding climate change, adaptation measures taken in response to these changes, and how well these perceptions correlate with meteorological data in Kenya. We find that a significant number of farmers perceive climate change as real, and that they are particularly concerned about changes in rainfall and temperature. Changing crop varieties is predominantly used as an adaptation measure since extension messages often encourage adoption of drought‐resistant varieties. Major factors influencing farmer perceptions include age of the farmer, which is often associated with more farming experience and subsequent extension service. Except in low potential zones, farmers' perceptions of climatic variability are in line with climatic data records. Better education, access to extension messages, farm size and credit facilities are necessary for farmers to decide to adapt to climate change. The paper further assesses barriers to the adoption of various adaptation strategies, and lack of finances and knowledge have been found to inhibit adaptation response within the smallholder farming sector. Findings imply that effective adaptation to threats posed by climate variability and change requires a multi‐dimensional collaborative approach, with different stakeholders playing key roles in providing support services in terms of education, extension, credit and meteorological information.